Peran Lembaga Penyiaran Publik (LPP) Rri Padang Dalam Mengedukasi Masyarakat Mengelola Sampah Limbah Covid-19 - Sally Dela Putri; yohanis; gusnayetti (Jurnal Administrasi Publik dan Pemerintahan, 2023)
The Covid-19 outbreak has hit Indonesia for almost three years. Although Covid-19 cases had fluctuated and were rumored to be heading for an endemic period, the Covid-19 virus had not disappeared, and even new variants were increasing. Under these conditions, the author did this thesis aimed to educate the public through radio broadcasts about the dangers of Covid-19 waste to human life. The research was carried out based on the academic calendar of STISIPOL-IB Padang from March 23 to May 31, 2022. Meanwhile, the object of the research and writing process was carried out at LPP RRI Padang. The technique used by the author is to use purposive sampling, namely by using people who represent the population. As for the selection, the speakers are competent, loyal listeners of LPP RRI Padang and the people of Padang City. Getting the data is done by observation, interview, and documentation study. In practice, the author makes a list of questions and addresses the resource person. The data collected were analyzed using descriptive qualitative analysis.